RagC GTPase regulates mTOR to promote chemoresistance in senescence-like HepG2 cells - Jiang, Wei; Ou, Zhenglin; Zhu, Qin; Zai, Hongyan (Frontiers in Physiology, 2022)
Radiotherapy and chemotherapy can arrest cancer cells in a senescence-like state, which can lead to therapy resistance and cancer relapse. mTOR is hyperactivated in senescent cells but the mechanisms remain unclear. In this study, we examine the roles of several mTOR-regulated GTPases in senescence-like liver cancer cells and the mechanisms of drug resistance. We show that although RagC, Rheb, Rab1A, Rab5, and Arf1 GTPases were required for optimal mTOR activation in proliferating HepG2 cells, only RagC and Rheb are required in the senescence-like counterparts. Consistently, the drug resistance of the senescence-like HepG2 can be reduced by knocking down RagC and Rheb but not the other GTPases. Autophagic and lysosomal activity were increased in senescence-like cells; pharmacological inhibition of autophagy-lysosome decreased mTOR activity and preferentially sensitized senescence-like HepG2 cells to chemotherapy drugs including trametinib, cisplatin, and doxorubicin. In liver cancer patients, expression of RagC and Rheb but not other GTPases examined was associated with unfavorable prognosis. Our study therefore has defined a key role of Rag-Rheb GTPase in mediating mTOR activation and drug resistance in senescence-like HepG2 cells, which could have important implications in developing second-line treatments for liver cancer patients.